Project Management Development – Practice and Perspectives: 10th International Scientific Conference on Project Management in the Baltic Countries. June, 2021, Riga, University of Latvia. Journal - University of Latvia; Professional Association of Project Managers (Latvia) (University of Latvia, Research Institute of the Project Management, 2021)
[Preface:] During the last year we continued to deal with the new challenges as during pandemic many projects and project managers faced problems what we all did not expect to happen. However, project management has always been a field what is flexible to changes and risk mittigations as those are cruical processes in any project. That is why this publication features experts experience with the use of agile methods, techniques, and formats in project development. They will review the agile project management practice in IT, services, construction, and other projects. The new formats additionally concentrate on the development of their standards of use and the problems arising in their practical application. The current global economy and growing digitalization require ever new solutions for cooperation between economy and society. In these terms, project management serves as a key discipline ensuring technically innovative and fast satisfaction of clients' demands. The classical project management methods are faced with certain changes in such circumstances. The new factors of success are agile and hybrid project management, as well as social competence and interactivity. The time of choosing between agile and traditional project management has already passed. Today, the tools to use for project management combine both agile and traditional elements. Pandemic thought as that risk management is still crucial in every project and right risk management actions should be impelemented. Proper risk management also requires proper risk management methodologies. Now agile methodology has its roots in the IT world. It has recently been adopted by other industries for more tangible projects and just larger projects overall. It is particularly useful in situations where there is a lot of unknowns, where project specs can change frequently and we can see that happening a lot when you have got your teams distributed over a wide geography or, some are remote, some are having to come in. (...)
Keywords: 650; Projektmanagement; Agilität; Digitalisierung